2015
DOI: 10.1164/rccm.201410-1771oc
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sphingolipids Associated with Chronic Obstructive Pulmonary Disease Phenotypes

Abstract: Rationale: Chronic obstructive pulmonary disease (COPD) occurs in a minority of smokers and is characterized by intermittent exacerbations and clinical subphenotypes such as emphysema and chronic bronchitis. Although sphingolipids as a class are implicated in the pathogenesis of COPD, the particular sphingolipid species associated with COPD subphenotypes remain unknown.Objectives: To use mass spectrometry to determine which plasma sphingolipids are associated with subphenotypes of COPD.Methods: One hundred twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
131
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 34 publications
10
131
4
1
Order By: Relevance
“…scribed [15]. Although we saw no significant change in serum SM levels in our mouse model of emphysema, a number of SMs were significantly reduced during the progression of emphysema more local to the lung (Figure 2A).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…scribed [15]. Although we saw no significant change in serum SM levels in our mouse model of emphysema, a number of SMs were significantly reduced during the progression of emphysema more local to the lung (Figure 2A).…”
Section: Resultsmentioning
confidence: 68%
“…To this end, there have been a number of studies published over the last few years assessing the COPD metabolome. This has included both untargeted [10][11][12][13] and targeted [14] metabolomics, as well as a combination of both [15] measured in either plasma or serum from COPD patients. In their combined approach, Bowler et al [15] reported a strong inverse association between the level of some plasma sphingomyelins (SMs) and emphysema in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheral blood mononuclear cell (PBMC) transcriptomic data was generated on the Affymetrix HGU133 Plus 2.0 array and normalized by measuring the geometric mean (Bahr et al, 2013). Metabolomic data from plasma was processed and generated using LC/MS Agilent software and tools and pre-processed and filtered using MSPrep (Bowler et al, 2015;Hughes et al, 2014). Both datasets were filtered based on Grubbs' outlier test, leaving 38 852 transcripts and 1640 metabolites (Grubbs' P-value > 0.05).…”
Section: Copd Transcriptomic and Metabolomic Datamentioning
confidence: 99%
“…Previous studies by COPDGene have implicated sphingolipids and their related pathways in COPD (Bowler et al, 2015). Sphingolipid-related metabolites were determined using ID Browser in Mass Profiler Professional (MPP) software (Agilent).…”
Section: Copd Transcriptomic and Metabolomic Datamentioning
confidence: 99%